Kirurška priprava atrofične maksile za vsaditev dentalnih implantatov - Žerdoner, Danijel (Zdravniški vestnik, 2004)
Background. Alveolar process atrophy is a physiological process in edentulous patients that may heavily compromise the succes of dental prosthetic rehabilitation. This is particulary important for insertion of endosseous implants. Because of the direct vicinity of maxillary sinuses, implantation isoften impossible without previous pre-prosthetic surgical intervention. Methods. Two types of pre-prosthetic surgical procedures are described and their relative advantages are discussed. An illustrative case report is presented, describing the patients problems, his treatment and clinical outcome. Conclusions. In cases when maxillary alveolar process atrophy is so severe that insertion of dental implants is impossible, surgical correction with sinus floor lift is necessary. In our institution, the results of this procedure are good. Good quality of the antral mucosa and normal anatomic shape of the maxillary sinuses are two prerequisites for its success.
Keywords: Adult; Alveolar Bone Loss; Alveolarna kost, izguba; Čeljust brezzoba, delno; Dental Implants; Jaw, Edentulous, Partially; Maksila; Maxilla; Odrasli; Surgery, Oral, Preprosthetic; Zobni vsadki